Upaya Tiongkok dalam Mengatasi Ketimpangan Pembangunan Antardaerah pada Masa Kepemimpinan Jiang Zemin dan Hu Jintao - Wibawa, Adi; Arisanto, Puguh Toko (Nation State: Journal of International Studies, 2019)
The Chinese economic revolution launched since 1978 by Deng Xiaoping put national economic growth as a priority but ruled out the aspect of equity which was one of the main characteristics of the socialist state. The reVolution resulted a spectacular national economic growth as well as inequality between regions in China. Therefore, the Chinese Government, since the leadership of Jiang Zemin and continued by Hu Jintao, has been trying to improve the condition. This article will explain the strategies and policies of equitable development between regions in China during the reign of Jiang and Hu. By using descriptive qualitative methods, the data used are secondary data obtained from official publications of the Chinese government and supported by scientific articles that can be accessed through the internet. The results obtained indicate the seriousness of the Chinese Government under Jiang and Hu in revising national development priorities. The target of economic growth is lowered and no longer became a priority of development programs. On the other hand, underdeveloped regional development programs such as infrastructure and industrial development are accelerated to catch up with the developed regions.